2020
DOI: 10.3390/ijms21176356
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids and Their Association with Signalling Pathways in Inflammation, Glucose and Lipid Metabolism

Abstract: Short-chain fatty acids (SCFAs), particularly acetate, propionate and butyrate, are mainly produced by anaerobic fermentation of gut microbes. SCFAs play an important role in regulating energy metabolism and energy supply, as well as maintaining the homeostasis of the intestinal environment. In recent years, many studies have shown that SCFAs demonstrate physiologically beneficial effects, and the signalling pathways related to SCFA production, absorption, metabolism, and intestinal effects have been discovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
387
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(398 citation statements)
references
References 138 publications
(155 reference statements)
3
387
0
8
Order By: Relevance
“…To date, the mechanism by which SCFAs inhibit HDACs is still unclear. It appears that SCFAs may directly act on HDACs via different transporters on the cells, or indirectly through GPCR activation ( 34 ). Our results, however, have indicated that SCFAs enter into target cells and act inside these cells, since we demonstrated that GPCRs were not involved in SCFA-induced responses ( Figure 5E ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the mechanism by which SCFAs inhibit HDACs is still unclear. It appears that SCFAs may directly act on HDACs via different transporters on the cells, or indirectly through GPCR activation ( 34 ). Our results, however, have indicated that SCFAs enter into target cells and act inside these cells, since we demonstrated that GPCRs were not involved in SCFA-induced responses ( Figure 5E ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to a lack of the enzymes essential for digestion of dietary fiber in the human gut, SCFAs are the primary metabolites from the fermentation of incompletely hydrolyzed dietary foods by specific gut microbiota in the colon through various pathways ( Table 1 ) [ 4 ]. The total concentration of SCFAs in the gut is 0.5–0.6 mol per day [ 24 ] depending on the diet, bacterial composition of the gut, and intestinal transit time [ 25 ]. Acetate (C2), propionate (C3), and butyrate (C4) are the most abundant SCFAs found in the gut (≥95%) with a molar ratio of roughly 3 : 1 : 1, respectively [ 3 ].…”
Section: Overview Of Scfasmentioning
confidence: 99%
“…The opposing enzymes, histone acetyltransferases (HATs), transfer the acetyl group of acetyl-CoA to histones, dissociate DNA from histone octamers, relax the nucleosome structure, make transcription factors bind to DNA-binding sites, and activate gene transcription. HATs and HDACs maintain acetylation of histone and nonhistone proteins in dynamic equilibrium to regulate physiological functions, such as inflammation, pancreas development, glucose metabolism, and insulin signaling [ 24 , 42 ]. However, overexpression and aberrant recruitment of HDACs are associated with T2DM pathogenesis [ 43 ].…”
Section: Overview Of Scfasmentioning
confidence: 99%
“…The participation of SCFAs in two major signaling pathways involved in metabolic inflammation, glucose, and lipid metabolism is well known [ 53 ]. Numerous studies have shown correlations between SCFAs, BMI, body fat distribution, and fat to lean mass ratio in children [ 54 ].…”
Section: Discussionmentioning
confidence: 99%